2009
DOI: 10.1038/sj.bjc.6605413
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cells are associated with increased risk of venous thromboembolism in metastatic breast cancer patients

Abstract: BACKGROUND: Cancer is a risk factor for venous thromboembolism (VTE). Circulating tumour cells (CTCs) are an independent predictor of survival in metastatic breast cancer (MBC) patients. The aim of this study was to test the hypothesis that CTCs are associated with the risk of VTE in MBC patients. METHODS: This retrospective study included 290 MBC patients treated in the MD Anderson Cancer Center from January 2004 to December 2007. Circulating tumour cells were detected and enumerated using the CellSearch syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 15 publications
(17 reference statements)
4
43
0
4
Order By: Relevance
“…Plasma level of apolipoprotein A-IV was found signiWcantly decrease in BRCA1 carriers compared to non-mutant controls. A previous study had reported an augmented expression of apolipoprotein A-IV in plasma from women with breast cancer (Mego et al 2009). However, there are also a great number of studies in diVerent types of cancer that support our results about apolipoprotein A-IV expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Plasma level of apolipoprotein A-IV was found signiWcantly decrease in BRCA1 carriers compared to non-mutant controls. A previous study had reported an augmented expression of apolipoprotein A-IV in plasma from women with breast cancer (Mego et al 2009). However, there are also a great number of studies in diVerent types of cancer that support our results about apolipoprotein A-IV expression.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these Wndings may suggest association between BRCA1 mutations and modiWcation in circulating biomarkers associated with predisposition of platelets to be activated. Accordingly, breast cancer has been associated with both arterial and venous thrombotic events (Mego et al 2009;Bourdeanu and Luu 2010). Some of the arterial and venous thrombotic events associated with breast cancer were attributed to inserted venous catheters, in patients receiving chemotherapy, to tamoxifen treatment, and to adjuvant chemotherapy treatment between others (Tesselaar et al 2004;Osborne 1998;Saphner et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…11,13,[17][18][19][20][21][22][23] However, EpCAM varies in expression level between cancers and potentially fails to capture more invasive CTCs that have undergone the epithelial-to-mesenchymal transition (EMT). [24][25][26] Despite differences in cell surface antigen expression levels, a majority of cancer cells are vastly different from blood cells in cellular composition and morphology, which leads to their distinct electrical properties and dielectrophoretic response. 27 Therefore, we hypothesize that dielectrophoresis (DEP) can potentially be used to capture cancer cells that are less likely to be isolated by traditional immunocapture methods with epithelial markers such as EpCAM.…”
mentioning
confidence: 99%
“…Kansere bağlı tromboembolik hastalıkların gelişiminde, kanser hücrelerinden salgılanan prokoagülan moleküller, tedavide büyük cerrahi girişimlerin uygulanması, hastanede yatış süresinin uzamış olması, santral venöz kateter kullanımı, kemoterapi ve hormonal tedaviler gibi risk faktörleri mevcuttur (15)(16)(17)(18)(19)(20)(21)(22). Kanser hücrelerinin VTE insidansını arttırmasının patogenetik mekanizmaları yüzyıldan fazla bir zaman önce Virchow tarafınca ortaya konmuştur.…”
Section: Gereç Ve Yöntemunclassified